The Effect of Ammonia Inhalants on Mental-Fatigue-Related Force Loss - Barnes MJ; O’Connor E; van Zanten J (MDPI (Basel, Switzerland), 2025)
Objectives: Ammonia inhalants (AIs) are commonly used in competition with the assumption that they will increase arousal and reduce the detrimental effects of mental fatigue on performance. However, as the effect of AIs on mental fatigue is unclear, this study investigated (1) whether mental-fatigue-related changes in mood states are associated with reductions in maximal lower-body force production and (2) whether AIs reduce any mental-fatigue-induced changes in performance. Methods: In a randomized, crossover designed study, nine resistance trained males completed two trials, with and without AIs. Profile of mood states, isometric midthigh pull force, and electromyography were measured before and after completion of a 75 min AX-continuous performance test (AX-CPT). For AI trials, AIs were used prior to post-AX-CPT IMTPs. Results: The AX-CPT significantly increased all negative mood subscales, while decreasing vigor (all p < 0.05), resulting in an increase in total mood disturbance (pre-AX-CPT: 27.1 ± 3.17 vs. post-AX-CPT: 64.49 ± 4.01; p = 0.005). Additionally, compared to baseline, force was reduced immediately (1699 ± 345 vs. 1521 ± 324 N; p = 0.009), but not five minutes post-AX-CPT (p = 0.328). Electromyography did not change over time, and no differences between treatments were evident for any of the measures. Conclusions: Mental fatigue, and related mood disturbance, has the potential to acutely reduce lower-body, maximal force. This finding may have implications for athletes competing in strength sports where mental focus, arousal and maximal force production determine optimal performance. However, AIs offer no benefit to alleviating the detrimental effects of mental fatigue.